Smart Shopping Cart Calculator using Barcode Scanner for Supermarkets in Kuching, Sarawak - Wang, Hui Hui; Wang, Yin Chai; Wee, Bui Lin; Chin, Xian Rong; Mengyun, Hu (Semarak Ilmu Publishing, 2025)
Nowadays, Supermarkets encountered a substantial increase in customer flow. Traditional shopping in crowded malls and supermarkets often involves time-consuming processes like selecting products, navigating heavy shopping carts, waiting in long checkout lines, and sometimes overspending. Despite online shopping's rise, many still prefer in-store shopping for product assessment. However, estimating costs and overspending are common issues. Introducing a smart shopping cart with a built-in calculator can enhance the shopping experience by enabling users to easily estimate their total expenses. This feature serves as a financial reminder, prompting shoppers to make informed decisions as they add items to their cart. It encourages thoughtful choices, reducing overspending and waste. This innovation can indirectly alleviate the issue of waste in low-income households. A survey in Kuching, Sarawak, found 90% of customers and management favoured introducing such technology, showing a demand for enhanced shopping experiences.